1984
DOI: 10.1111/j.1365-2265.1984.tb03235.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral Glucose Inhibits Growth Hormone Secretion Induced by Human Pancreatic Growth Hormone Releasing Factor 1–44 in Normal Man

Abstract: The interaction between the inhibitory effect on growth hormone secretion of a 75 g oral glucose load and the stimulatory effect of human pancreatic growth hormone releasing factor 1-44 (hpGRF 1-44, 10 micrograms i.v.) has been studied in six normal subjects. hpGRF 1-44 alone induced a rise in growth hormone concentrations (maximum mean +/- SEM, 16.5 +/- 1.7 mU/l 15 min after injection) while growth hormone levels were suppressed by oral glucose alone (less than 1.5 mU/l from 45 to 135 min after glucose ingest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
26
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 14 publications
1
26
1
Order By: Relevance
“…In the human, acute hyperglycemia blocks GHRH-induced GH release, which excludes the possibility that glucose may act by inhibiting endogenous GHRH release (3,4,28). These reports suggested that glucose might act in a manner similar to free fatty acids (29), that is, by directly inhibiting pituitary somatotropes or by inducing hypothalamic SRIH release, or by a combination of both mechanisms.…”
Section: Discussionmentioning
confidence: 92%
“…In the human, acute hyperglycemia blocks GHRH-induced GH release, which excludes the possibility that glucose may act by inhibiting endogenous GHRH release (3,4,28). These reports suggested that glucose might act in a manner similar to free fatty acids (29), that is, by directly inhibiting pituitary somatotropes or by inducing hypothalamic SRIH release, or by a combination of both mechanisms.…”
Section: Discussionmentioning
confidence: 92%
“…However, the mechanism of the suppressing effect of hyperglycemia on GH secretion in normal subjects is not clear, nor is the cause of paradoxical secretion to oral glucose in acromegaly [13][14][15]. It was reported that an acromegaly induced by an ectopic GRHproducing tumor, had a paradoxical GH secretion to oral glucose, but that an exogenous GRH load did not induce GH secretion, therefore GRH was thought not to be involved in the paradoxical GH response to oral glucose load in acromegaly [16].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, before the development of accurate assays for IGF-I measurement, dynamic testing of the GH response to glucose suppression had been used extensively to provide evidence of normal GH secretory dynamics (18,19). Acute elevation of plasma glucose is known to suppress plasma GH secretion in normal subjects (15,20,21). This suppression may be mediated through glucoreceptors in the ventromedial nucleus of the hypothalamus partly via a rise in hypothalamic somatostatin secretion (22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%